Football Talent Identification (FootNet) - Halmi, Muhammad Hazrin (IRC, 2020)
Platform such as application are software specifically design for mobile device. This paper will discuss the use of application for leveraging social network among the football community. Before the advent of modern-day technology, football community unable to fully utilize their skill, because the lack of assistance and options, However, immense opportunities are being provided by the technologies which play an important role in football community development. This paper explore way to utilise the current technology to the upper level by using the application to allow the football community to interact using the professional network platform. This paper aims to conduct a study of football community and association on how they make use of social football player that have future prospect to their full potential. In order to figure out them, the survey, and interview are used in our study. The interviewees are the head of information technology department of Football Association of Malaysia (FAM) that are more competent to give explanation regarding the football talent identification in Malaysia. The survey is conducted in which consist of 40 respondents.